Hepatitis B e Antigen Induces NKG2A+ Natural Killer Cell Dysfunction via Regulatory T Cell-Derived Interleukin 10 in Chronic Hepatitis B Virus Infection - Ma, Qingqing; Dong, Xiaoyu; Liu, Siyu; Zhong, Tao; Sun, Dandan; Zong, Lu; Zhao, Changcheng; Lu, Qiong; Zhang, Min; Gao, Yufeng; Ye, Ying; Cheng, Jun; et al. (Frontiers in Cell and Developmental Biology, 2020)
Although persistent hepatitis B virus (HBV) infection is associated with natural killer (NK) cell dysfunction, whether HBV viral antigens are responsible for NK cell dysfunction in patients with chronic hepatitis B (CHB) remains obscure. In this study, we found that increased percentages of NK cells expressing the inhibitory receptor, NKG2A, were accompanied by restored NK cell function, through blocking NKG2A in patients with CHB infection. Further, the percentage of NK cells expressing NKG2A was positively correlated with regulatory T cell (Treg) numbers and levels of secreted interleukin-10 (IL-10) in patients with CHB. Moreover, exposure of peripheral blood mononuclear cells (PBMCs) isolated from healthy controls to CHB serum resulted in increased proportions of NKG2A+ NK cells, while blocking IL-10 reduced NKG2A+ and increased IFN-γ+ NK cells. Further, stimulation of NK cells and Tregs from healthy controls with CHB serum and anti-IL-10 resulted in increased IFN-γ production in the culture supernatant. The frequencies of NKG2A+ NK cells and IL-10+ Tregs were significantly increased, along with serum alanine transferase and HBV DNA levels in patients with CHB positive for the Hepatitis B e antigen (HBeAg, a marker of viral replication) relative to those who were HBeAg-negative. Importantly, exposure of PBMCs from healthy controls to HBeAg resulted in increased IL-10 production, accompanied by reduced TNF and IFN-γ levels, while the levels of cytokine in culture supernatant were recovered by addition of anti-IL-10. Similarly, stimulation of NK cells and Tregs from healthy controls with HBeAg resulted in decreased TNF and IFN-γ levels, while IL-10 blockade increased TNF and IFN-γ secretion. We conclude that HBeAg induces IL-10 production by Tregs, thereby leading to increased NKG2A expression on NK cells, which contributes to NK cell dysfunction during CHB infection. These data suggest that HBeAg is associated with NK cell dysfunction in CHB.